Signals selection of TCSC device for damping oscillation - Magaji, Nuraddeen (ACEEE, USA, 2010)

(untitled)
This paper proposes Eigen value analyses to assess the most appropriate input signals (stabilizing signal) for supplementary damping control of TCSC. The Right- Half Plane zeros (RHP-zeros) and Hankel Singular Value (HSV) is used as tools to select the most receptive signal to a mode of the Interarea oscillation. The effectiveness of the proposed method of selection of signals is demonstrated on practical network of 25 bus south Malaysian Power system.